2014
DOI: 10.1016/j.vaccine.2014.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of vaccine efficacy by expression of a TLR5 ligand in the defined live attenuated Francisella tularensis subsp. novicida strain U112ΔiglB::fljB

Abstract: Oral vaccination with the defined live attenuated Francisella novicida vaccine strain U112▲iglB has been demonstrated to induce protective immunity against pulmonary challenge with the highly human virulent F. tularensis strain SCHU S4. However, this vaccination regimen requires a booster dose in mice and exhibits 50% protective efficacy in the Fischer 344 rat model. To enhance the efficacy of this vaccine strain, we engineered U112▲iglB to express the Salmonella typhimurium FljB flagellin D1 domain, a TLR5 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…This has been accompanied by a substantial increase in publications on development of tularemia vaccines, mostly on live attenuated vaccine candidates, including defined mutants of F. tularensis subsp. holarctica (Bakshi et al, 2006 , 2008 ; Pechous et al, 2006 , 2008 ; Li et al, 2007 ; Sebastian et al, 2007 , 2009 ; Meibom et al, 2008 ; Sammons-Jackson et al, 2008 ; Santiago et al, 2009 ; Jia et al, 2010 ; Zarrella et al, 2011 ; Kim et al, 2012 ; Schmitt et al, 2012 ; Barrigan et al, 2013 ; Golovliov et al, 2013 ; Mahawar et al, 2013 ; Straskova et al, 2015 ; Suresh et al, 2015 ), F. novicida (Pammit et al, 2006 ; Tempel et al, 2006 ; Mohapatra et al, 2007 ; Quarry et al, 2007 ; Kanistanon et al, 2008 ; West et al, 2008 ; Cong et al, 2009 ; Sanapala et al, 2012 ; Signarovitz et al, 2012 ; Chu et al, 2014 ; Cunningham et al, 2014 ), and subsp. tularensis (Twine et al, 2005 , 2012 ; Qin et al, 2008 , 2009 ; Conlan et al, 2010 ; Michell et al, 2010 ; Shen et al, 2010 ; Ireland et al, 2011 ; Rockx-Brouwer et al, 2012 ; Reed et al, 2014 ; Santiago et al, 2015 ), but also on live attenuated heterologous vaccines expressing F. tularensis proteins (Jia et al, 2009 ; Kaur et al, 2012 ; Banik et al, 2015 ) and recombinant LVS vaccines expressing F. tularensis proteins (Jia et al, 2013 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This has been accompanied by a substantial increase in publications on development of tularemia vaccines, mostly on live attenuated vaccine candidates, including defined mutants of F. tularensis subsp. holarctica (Bakshi et al, 2006 , 2008 ; Pechous et al, 2006 , 2008 ; Li et al, 2007 ; Sebastian et al, 2007 , 2009 ; Meibom et al, 2008 ; Sammons-Jackson et al, 2008 ; Santiago et al, 2009 ; Jia et al, 2010 ; Zarrella et al, 2011 ; Kim et al, 2012 ; Schmitt et al, 2012 ; Barrigan et al, 2013 ; Golovliov et al, 2013 ; Mahawar et al, 2013 ; Straskova et al, 2015 ; Suresh et al, 2015 ), F. novicida (Pammit et al, 2006 ; Tempel et al, 2006 ; Mohapatra et al, 2007 ; Quarry et al, 2007 ; Kanistanon et al, 2008 ; West et al, 2008 ; Cong et al, 2009 ; Sanapala et al, 2012 ; Signarovitz et al, 2012 ; Chu et al, 2014 ; Cunningham et al, 2014 ), and subsp. tularensis (Twine et al, 2005 , 2012 ; Qin et al, 2008 , 2009 ; Conlan et al, 2010 ; Michell et al, 2010 ; Shen et al, 2010 ; Ireland et al, 2011 ; Rockx-Brouwer et al, 2012 ; Reed et al, 2014 ; Santiago et al, 2015 ), but also on live attenuated heterologous vaccines expressing F. tularensis proteins (Jia et al, 2009 ; Kaur et al, 2012 ; Banik et al, 2015 ) and recombinant LVS vaccines expressing F. tularensis proteins (Jia et al, 2013 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study indicated that a mutant of F. novicida U112 expressing flagellin of Salmonella typhimurium could activate TLR5 resulting in increased inflammation, and therefore, this strain may be a potent tularemia vaccine candidate. 22 The possibility exists that F. tularensis LVS / pGFLI may also provide increased protection against F. tularensis for similarly stimulating TLR5, however this remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…leads to faster clearance of the infection (132), and it was later revealed that TLR5 activates antigen-presenting cells, increasing T cell response (133) (manuscript in preparation), and may ultimately contribute to the more rapid clearance previously reported. In several other microorganisms, the addition of TLR5 agonists have resulted in an increased performance of the vaccine (134)(135)(136)(137)(138)(139)(140)(141). Altogether these data suggest that TLR5 agonists could significantly increase the performance of the current acellular pertussis vaccine.…”
Section: Toll-like Receptors Agonistsmentioning
confidence: 90%